Vida no Espírito e compromisso social em São João Crisóstomo: análise a partir das homilias sobre a Carta aos Romanos, capítulo oito - Santos, José Rogério Soares dos (2014)
The Life in the Spirit has implications that go beyond a subjective experience of faith. The experience that takes place within the hearts and that makes the one who has been baptized desire intimacy with God, should be manifested by a new manner of living and behaving in society. Moved by divine charity, the Christian cannot retreat into an isolated, intimist experience. According to St John Chrysostom, the possibility of a new world on the Earth is real, by means of the works of the Spirit. This new world, however, is temporal and transient, the firstfruits of the eternal Kingdom prepared by Christ for those who live such new life. Strugling for a better and fairer polis on the Earth will always be necessary, with the awareness that it is just the firstfruits of that eternal polis (cf. Phil 3, 20) for which we have been saved